Republic of Moldova : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
This Selected Issues paper analyzes the macroeconomic impact of workers' remittances on Moldova. The paper focuses on Moldova's labor emigration since the late-1990s using survey data designed to shed light on the economic and social consequences of migration. The survey results are broadly consistent both with the findings from balance-of-payments data and with the stylized facts in the labor migration literature. The paper also examines various indicators to assess the appropriateness of the current exchange rate level.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet